ECOLOGICAL NICHE THEORY (Nichespace, Niche Breadth and Niche Overlap, Competitive Superiority) Local Media in Central Java (Suara Merdeka And Tribun Jateng) - Monicaningsih, Aisyah (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
ABSTRACTThe Central Java Province has a wide range of local media both print and electronic media. The print media in Central Java is growing rapidly, as are present in the data follows the various print media market in Central Java. Suara Merdeka is one of the well-known mass media in Central Java Province, and is a daily morning newspaper published in the city of Semarang, Central Java. This daily has a circulation limited to the area of Central Java. The other one Tribun Jateng newspaper is a network Tribunnews newspaper, Kompas Gramedia Group. With the tagline